Glutathione is a potential therapeutic target for acrolein toxicity in the cornea. (1st April 2021) - Gupta, Suneel; Kamil, Sabeeh; Sinha, Prashant R.; Rodier, Jason T.; Chaurasia, Shyam S.; Mohan, Rajiv R.
Graphical abstract: Highlights: Acrolein exposure causes oxidative stress in human corneal stromal fibroblasts. Oxidative stress leads mitochondrial dysfunction and cause cell death after acrolein exposure. Glutathione can be a potential target to limit acrolein toxicity in human cornea. Abstract: Toxic and volatile chemicals are widely used in household products and previously used as warfare agents, causing a public health threat worldwide. This study aimed to evaluate the extent of injury and mechanisms of acrolein toxicity in the cornea. Primary human corneal stromal fibroblasts cultures (hCSFs) from human donor cornea were cultured and exposed to acrolein toxicity with -/+ N-acetylcysteine (NAC) to study the mode of action in the presence of Buthionine sulphoximine (BSO). PrestoBlue and MTT assays were used to optimize acrolein, NAC, and BSO doses for hCSFs. Cell-based assays and qRT-PCR analyses were performed to understand the acrolein toxicity and mechanisms. Acrolein exposure leads to an increased reactive oxygen species (ROS), compromised glutathione (GSH) levels, and mitochondrial dysfunction. The TUNEL and caspase assays showed that acrolein caused cell death in hCSFs. These deleterious effects can be mitigated using NAC in hCSFs, suggesting that GSH can be a potential target for acrolein toxicity in the cornea.